Evaluasi Produksi Video UMKM Jasijuka di Facebook - Bagas Radityo Wicaksono; Agustrijanto (UNIVERSITAS KALBIS, 2022)
MSME Jasijuka produces videos to convey their videos through Facebook, but the results are not optimal. The purpose of the production of this promotional video is to market the product so that it is well known by the public. This study uses a model theory production of Herbert Zettl and using the basic concept of evaluation, video production, facebook and SMEs. This study uses a post-positivism paradigm, with a methodical approach qualitative (case study). The results of this study indicate that the video production of the Jasijuka MSME is still carried out in conservative ways, namely not yet structured, not using concepts and scripts, and not using proper planning and video production processes. Video production is only limited to recording, so that MSME Jasijuka has the impression of suddenly making videos. Video production materials often contain product processing that is not supported by a structured storyline and messages and graphics are still monotonous.